2022
DOI: 10.1002/tea.21828
|View full text |Cite
|
Sign up to set email alerts
|

Students' engagement with Socioscientific issues: Use of sources of knowledge and attitudes

Abstract: The current study is about students' engagement with socioscientific issues (SSI). We explored the use of sources of knowledge about SSI and attitudes toward SSI among a sample of 1676 Dutch 8‐ to 16‐year‐old students. First, we developed a questionnaire that measured students' use of four sources of knowledge about SSI: Social Resources (online media use and talking with parents and friends), In‐Class Resources (in‐class talk and in‐class offline media use), Visit Resources (visiting the zoo or a science muse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 89 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…Students' SSI‐related resources will differ quantitatively and qualitatively. Quantitatively, some students may have more access to resources (e.g., knowledge of particular SSI) and others less (Klaver et al, in press). Qualitatively, there may be differences in resources that relate to, for example, students' political affiliations (Walsh & Tsurusaki, 2018), cultural background (Evagorou et al, 2012), or the particular media sources they follow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students' SSI‐related resources will differ quantitatively and qualitatively. Quantitatively, some students may have more access to resources (e.g., knowledge of particular SSI) and others less (Klaver et al, in press). Qualitatively, there may be differences in resources that relate to, for example, students' political affiliations (Walsh & Tsurusaki, 2018), cultural background (Evagorou et al, 2012), or the particular media sources they follow.…”
Section: Discussionmentioning
confidence: 99%
“…Operationalizations of SSC can be supported by our conceptualization of SSC with its distinction between internal and external resources. For instance, in our empirical study about students' SSC, we investigated among a large sample how often students use sources of knowledge and how this related to their attitudes toward SSI (Klaver et al, in press). The overview of SSC provided in Figure 1 clarifies that Klaver et al (in press) investigated the relation between students' use of external resources and a type of internal resource.…”
Section: Discussionmentioning
confidence: 99%
“…It was also recently found that Dutch students from primary and secondary school hardly discuss sustainability and other SSIs with friends on their own initiative (Klaver et al, 2022).…”
Section: Ec and Studentsmentioning
confidence: 99%